Iron Intake and Its Correlation to Ferritin and Hemoglobin Level among Children Aged 24–36 Months in Jakarta in 2020 - Jessica Ferdi; Saptawati Bardosono; Bernie Endyarni Medise (Indonesian Nutrition Association, 2021)
Introduction: Iron is essential for childâ€™s development and growth. Childrenâ€™s iron requirements are secured from daily food intake that might be affected by Covid-19 pandemic. This study aims to determine iron intake and its relationship with ferritin and hemoglobin levels as indicators of iron status among children in Jakarta.Method:Â This cross-sectional study was conducted in Kampung Melayu, Jakarta from September to October 2020. Seventy seven healthy children aged 24â€“36 months were taken using total population sampling method. Interviews were conducted to obtain characteristics data and iron intake using a semi-quantitative-food frequency questionnaire (SQ-FFQ). Blood tests are performed to check the levels of ferritin (controlled by hs-CRP value), and hemoglobin.Pearsonâ€™s/Spearmanâ€™s correlation test was performed using SPSS version 20.0.Â Result:Â Median of iron intake was 9.6 (1.5â€“40,7) mg/day, in which 33.8% of subjects was below the Indonesian Recommended Dietary Allowance (RDA) recommendation. The median ferritin value was 18.1 (1.4â€“91.1)Â ðœ‡g/L and the hemoglobin was 11.8 (6.6â€“15.2) g/dL, in which 40.3% and 27.3% subjects with iron insufficient-deficient and anemia, respectively. There wereÂ Â positive correlations between iron intake and ferritin (r = 0.328, p = 0.002) and iron intake and hemoglobin (r = 0.308, p = 0.003). A strong positive correlation was found between ferritin and hemoglobin (r = 0.769, p < 0.001).Conclusion: Iron intake of children aged 24â€“36 months had a weak positive correlation with ferritin and hemoglobin level.Â Keywords:Â children 24â€“36 months, ferritin, hemoglobin, iron intake, Jakarta